Phosophorus availability curve in the soil (Research, Society and Development, 2024)
The objective of this research was to evaluate the efficiency of different sources of phosphorus in the development of corn (Brevant Hybrid B2401PWU) in soil previously cultivated with pastures in the municipality of Paraguaço/MG. The design was in randomized blocks with a 3x2 factorial scheme, considering three sources of phosphorus (Fosbio®BR, Fosfato natural, Mono Ammonium Phosphate - MAP) and a control, with and without the presence of corn. The soil was prepared and the plots, measuring 4 m², received different treatments to increase the phosphorus content to 15 mg/dm³. Corn was sown in March 2024, and phosphorus sources were applied shortly after. Soil analysis was performed weekly, using 10 subsamples per plot to assess phosphorus availability over eight weeks. The data were subjected to statistical analysis using the Scott-Knott test at 5% probability. The results indicated that Fosbio®BR presented the highest average values ​​of phosphorus availability, especially in weeks 2 and 3, suggesting a controlled release of the nutrient, favoring corn development. Fosfato natural showed a rapid initial release of phosphorus, followed by a sharp decrease, which indicates lower efficiency over time. MAP showed a moderate and stable release of phosphorus, while controls maintained low levels of nutrient availability, as expected. It should be noted that although Fosbio® has given good results, the dosage is large to apply and this can be an operational and cost complication.